Promosi Pariwisata Bali Utara Berbasis Sastra Melalui Novel “Aku Cinta Lovina” dan “Rumah Di Seribu Ombak” - Arini, Ni Nyoman; Darma Putra, I Nyoman; Bhaskara, Gde Indra (Jurnal Master Pariwisata (JUMPA), 2021)
Tourism promotion can be actualized through brochures, advertising, films, literary works, and works of art by doing direct marketing or word of mouth recommendations to promote local tourist attractions. Literary works can also describe tourist attractions through myths, folklore, travel books, novels, and films. This study analyzed the promotion of North Bali tourism through novels. The novels used as research objects are the novel Aku Cinta Lovina by Sunaryono Basuki and Rumah di Seribu Ombak by Erwin Arnada. The novel Aku Cinta Lovina is considered as tourism promotion because it has a background story in Lovina, describing the tourist attraction of North Bali, the interaction between local people and foreign tourists, cultural diversity, the hospitality of the local people, and the story of cross-country travel between European tourist and Balinese girl. Meanwhile, the novel entitled Rumah di Seribu Ombak has been adapted into a film with the same title. The best-selling novel took the location of filming, most of which took place in North Bali. This study aimed to examine tourism in North Bali through the novel Aku Cinta Lovina and Rumah di Seribu Ombak as a literature-based medium for promoting tourism in North Bali. This study also contained the opinions of stakeholders related to tourism promotion through novels. The main theory used in this research is literary tourism theory, supported by promotion theory, host and guest theory. The relevant research approach used in this study was qualitative. The data analysis technique in this study used Content Analysis. Data were collected through observation, interviews, and documentation. This study concludes that the story's content in the novel Aku Cinta Lovina and Rumah di Seribu Ombak depicts natural and cultural tourist attractions, promoting North Bali tourism through natural beauty history, tradition, and culture of the local community. Keywords: literary tourism, North Bali tourism, tourism promotion.